Sosialisasi Kepemimpinan Bagi Pengurus OSIS SMP : Membangun Pemimpin Masa Depan Yang Berkarakter dan Inovatif - Febriyanto Febriyanto; Wiwin Karlina; Psycel Zahqindi Gea Kencana; Yoga Pratama; Latifah Latifah; Muhammad Marchio Lubis; M Fathur Ramadan (Lembaga Pengembangan Kinerja Dosen, 2024)
The Intra-School Student Organization (OSIS) at the junior high school level plays a crucial role in developing students' leadership skills. However, a lack of understanding of leadership concepts and minimal practical training are major obstacles to developing this potential. This research aims to enhance the leadership competencies of OSIS board members at SMP Negeri 1 Sumberrejo through a leadership socialization and training program. The implementation method used involves socialization and interactive discussions with all OSIS board members as participants. The results of the activities show that the socialization successfully increased participants' understanding of leadership concepts, ethics, responsibilities, and basic leadership skills such as effective communication, decision-making, and teamwork. The interactive Q&A sessions and distribution of door prizes also played a role in increasing participants' engagement and motivation. It is hoped that this activity will foster the development of strong, innovative leaders who are ready to face future challenges.